Accelerated human epidermal turnover driven by increased hyaluronan production. Issue 2 (February 2021) - Endo, Yoko; Yoshida, Hiroyuki; Ota, Yukiko; Akazawa, Yumiko; Sayo, Tetsuya; Hanai, Ushio; Imagawa, Kotaro; Sasaki, Masashi; Takahashi, Yoshito
Highlights: Hyaluronan (HA) is an essential component of extracellular matrix in the skin. 1-ethyl-β- N -acetylglucosaminide (β-NAG2) is a selective inducer of HA production. β-NAG2 increased epidermal HA and thickness in reconstructed human skin equivalents. Epidermal proliferation and differentiation were promoted via enhanced HA production. Epidermal HA production plays a key role in epidermal morphogenesis and homeostasis. Abstract: Background: Hyaluronan (HA) is an essential component of extracellular matrix in the skin, but its functions in the epidermis remain elusive. Objective: We examined the interaction of increased HA production mediated by 1-ethyl-β- N -acetylglucosaminide (β-NAG2), a newly developed highly selective inducer of HA production which is intracellularly converted to UDP- N -acetylglucosamine, a substrate of HA, with epidermal proliferation and differentiation. Methods: The amount, molecular size and epidermal tissue distribution of HA and expression of CD44, a cell surface receptor for HA, were analyzed in β-NAG2-treated organ cultured human skin, reconstructed human skin equivalents or cultured human skin keratinocytes. The relationship between HA and epidermal proliferation or differentiation was examined. Results: β-NAG2 significantly increased HA production in the epidermis of skin explants or skin equivalents without affecting molecular size of HA (>2000 kDa) or CD44 mRNA expression. Histochemical experiments revealed that β-NAG2 enhances HA signals in the basal to granular layers of the epidermis of skin equivalents, accompanying increased epidermal stratification. Immunohistochemical experiments demonstrated that signals of Ki67, transglutaminase 1 and filaggrin are increased in β-NAG2-treated skin equivalents, and these observations were confirmed by the data showing that mRNA expression of PCNA, transglutaminase 1 (TGM1) and filaggrin (FLG) is significantly up-regulated by β-NAG2 in skin equivalents. Importantly, blockade of HA production by inhibiting conversion of β-NAG2 to UDP-NAG abolished β-NAG2-mediated up-regulation of PCNA, TGM1 and FLG mRNA expression in cultured keratinocytes. Conclusion: These results suggest that increased epidermal HA production plays a key role in epidermal morphogenesis and homeostasis by accelerating keratinocyte proliferation and differentiation.